Pelatihan Pembuatan Website Sederhana di SMA Assaadah Pesantren Assaadah Puri Serpong Tanggerang Selatan - Wawan Budiarto; Deden Rosid Waltam (Pusat Riset dan Inovasi Nasional, 2024)
Website training can be one of the trainings that can be developed by students because with this training students have promising competency advantages. If students become graduate of school, they can later develop the website. If in the Islamic boarding school environment the graduate of school are spread across various regions and are trying in various fields, of course they need a website as a means of promotion. Moreover, now that many new business fields are being built, the need to create websites for promotion is increasing. However, sometimes the website training that is carried out does not develop as expected. The business being run is stagnant and even tends to decline. This is due to several things, namely technical aspects and management aspects. Partners in this PKM activity are SMA Assaadah Puri Serpong within the Assaadah Islamic Boarding School environment. Based on the results of observations and discussions with partners, there are several problems faced in the process of creating websites, databases, computer equipment, website design, execution processes and marketing websites that will be promoted to other parties. The absence of adequate technical knowledge of website training means that website training is carried out without proper planning and supervision. Another problem is that currently website hosting costs are expensive, which interferes with the website launching process. The solutions in this PKM activity are as follows: 1. Technical aspects: In accordance with the problems faced by partners, the solutions include: a. create a website creation material module guide. b. Selecting a computer with adequate specifications. c. by using applications that are simpler than other applications, namely HTML websites, PHP databases, WordPress hosting. 2. Management aspect: The solution is to provide business management training, including planning and control, both in the production and marketing aspects of a website that is ready to be launched.